HUBUNGAN KERJASAMA ORANG TUA DENGAN PERKEMBANGAN ANAK USIA DINI DI KELOMPOK BERMAIN - Islamiyati, Islamiyati (Jurnal Pendidikan Usia Dini, 2018)
The study aims to determine the relationship of parents cooperation with the development of early childhood in the playgroup in the working area of Metro Health Center. This study used an analytic cross-sectional method. The samples are all of the members of a playgroup in 9 playgroups in working area of Metro Health Center with 147 children. The data collection used is a questionnaire and the filling methods are in the form of checklist and observation. These studies are conducted in May - June 2015. The data analysis used is chi-square analysis. The resulting study shows that 50% of childhood development is suitable for his growth and development. Most of parents cooperation are still not good. The correlation between parents cooperation with child development will help the children develop optimally. It is suggested that the teacher of the school improve the cooperation with the parents. Keywords: Playgroup, the cooperation of parents, development, early childhood Penelitian ini bertujuan untuk mengetahui hubungan kerjasama orang tua dengan perkembangan anak usia dini di Kober wilayah kerja Puskesmas Metro. Metode penelitian yang digunakan analytic cross sectional. Sampel sebanyak 147 orang berasal dari 9 Kober di wilayah kerja Puskesmas Metro. Pengumpulan data menggunakan kuesioner dan cara pengisian dalam bentuk checklist dan observasi. Penelitian dilaksanakan pada Bulan Mei – Juni 2015. Analisa data menggunakan analisis chi square. Hasil penelitian diperoleh informasi 50% perkembangan anak sesuai dengan tumbuh kembang. Kerjasama orang tua sebagian besar kurang baik. Kerjasama orang tua dengan pihak Kober dapat membantu perkembangan anak yang optimal. Disarankan pihak sekolah meningkatkan kerjasama dengan orang tua. Kata Kunci: Kober, kerjasama orang tua, perkembangan, anak usia dini